Analisa Potensi Embung Itera Sebagai Pembangkit Listrik Tenaga Pico Hydro (PLTPH) - Corio, Dean; Kananda, Kiki; Salsabila S, Khansa (JURNAL NASIONAL TEKNIK ELEKTRO, 2019)
Institut Teknologi Sumatera (ITERA) has 5 reservoirs with lip embankment construction higher than the normal water level and have steep elevations with different catchment areas (DTA). By using the Google Earth Pro software, it is known that DTA reservoirs A, B, C, D, and E are respectively 1.728 ha; 1,146 ha; 1,052 ha; 0.844 ha; and 9.562 ha. This study aims to determine the potential energy that might be generated from the 5 reservoirs while still considering the integrity of the ecosystem. The power plant is in the form of a Pico hydro power plant that can be used as a power plant practicum media by Itera students, especially electrical engineering study program students. The power plant's rapid pipe is designed to be installed 1 meter below the normal water level and the operating time is based on the rain discharge that is accommodated by the reservoir in one month. The method used is field observation, rainfall data collection, calculations using practical rational methods and hydropower hydraulics. The results of data processing of five reservoirs owned by ITERA show that the greatest potential that can be used as a source of electricity generation is reservoirs E. The analysis shows that the discharge capacity of 0.216 m3 / s and an effective head of 5.46 m can produce an electric power generated of 7,071 kW with operational time at April.Keywords : Discharge, Rain Intensity,  Pico Hydro.AbstrakInstitut Teknologi Sumatera (ITERA) memiliki 5 embung dengan konstruksi bibir embung  lebih tinggi dari batas muka air normalnya serta memiliki elevasi curam dengan luasan Daerah Tangkapan Air (DTA) masing masing-nya berbeda. Melalui software Google Earth Pro diketahui luas DTA embung A, B, C, D, dan E secara berturut-turut yaitu 1,728 ha; 1,146 ha; 1,052 ha; 0,844 ha; dan 9,562 ha. Penelitian ini bertujuan untuk mengetahui potensi energi yang mungkin dibangkitkan dari 5 embung tersebut dengan tetap mempertimbangkan keutuhan ekosistemnya. Pembangkit berupa pembangkit listrik tenaga pico hydro yang dapat  digunakan sebagai media praktikum pembangkit tenaga listrik oleh mahasiswa Itera, khususnya mahasiswa program studi teknik elektro. Pipa pesat pembangkit listrik didesain terpasang 1 meter dibawah muka air normal dan waktu pengoperasian berdasarkan debit hujan yang tertampung oleh embung dalam satu bulan. Metoda yang dilakukan adalah observasi lapangan, pengumpulan data curah hujan, perhitungan menggunakan metode rasional praktis dan persamaan daya hidraulik tenaga air. Hasil pengolahan data lima embung yang dimiliki Itera didapatkan potensi terbesar yang bisa dimanfaatkan sebagai sumber pembangkit listrik adalah embung E. Hasil analisa menunjukkan debit tampungan 0,216 m3/s dan head efektif 5,46 m dapat menghasilkan daya listrik terbangkitkan sebesar 7,071 kW dengan waktu operasional pada bulan April.Kata Kunci : Debit, Intensitas Hujan, Pico Hydro.